Impedance of latex exudation by the bark excision wound during tapping - Yeang H Y (Journal of Natural Rubber Research, 1986)
The surfaces of the tapping cuts on Tjir 1 and RRIM 623 trees were scraped immediately after tapping to enhance wounding arising from excision of the bark shavings. A marked increase in the rate of latex vessel plugging and a decrease in yield were observed, suggesting that wounding the surface of the tapping cut contributed towards latex vessel plugging . Re-tapping GT1 and RRIM 501 trees 80 min after the initial tapping, before flow from the initial tapping had ceased, extended the flow duration. However, GT 1 trees that were re-tapped 20 min after the initial tapping did not show an increase in flow duration. In fact, a significant decrease was observed in RRIM 501 trees that were similarly treated. This suggests that wounding arising from bark exicision during tapping as a significant role in latex vessel plugging and the restiction of latex outlfow. Impedence of latex flow is possibly mediated through destabilisation of latex by coagulants released by the injured bark tissue.
Keywords: Bark excision; Latex exudation; Tapping